The Impact of West Bank Settlements on Israeli National Security - Kohavi, Itai; Nowiak, Wojciech (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2017)
Since the 1967 war in the Middle East, The Israeli settlements in the West Bank have always been one of the most controversial topics in the Israeli-Palestinian conflict. This article deals with the question: What is the impact of the West Bank settlements on the national security of Israel? The approach used to explore these issues is face-to-face in-depth interviews, during 2016, with 27 high-ranking Israeli Generals from the Military Intelligence (Aman), the National Intelligence Agency (Mossad), the Internal Security Agency (Shabak), the National Security Council (Malal), the Planning Branch of the General Staff (Agat), and the Prime Minister’s close circle of advisors. The interviews revealed three perspectives on the importance of the settlements for the Israeli national security. The first, views the settlements as a contribution to the national security of Israel, the second, views the settlements as a heavy national security liability, and the third, views the question as an irrelevant one, explaining that no one asks if Tel Aviv is important for the national security of Israel. As securitization of political messages is arguably at least as common in Israel as in other countries, with immediate national security challenges, the detailed perspectives of the Israeli National Security Elite (INSE) helps to extract the professional security rationales from the misleading political clatter. The article can be of interest to policy makers and researchers who deal with national security in general and in the Israeli-Palestinian conflict in particular.

Począwszy od wojny sześciodniowej z 1967 roku, osiedla izraelskie na Zachodnim Brzegu stały się jednym z najbardziej kontrowersyjnych zagadnień konfliktu Izraelsko-Palestyńskiego. Artykuł ten jest próbą odpowiedzi na następujące pytanie: Jaki jest wpływ osiedli usytuowanych na Zachodnim Brzegu na bezpieczeństwo narodowe Izraela? Dążeniem do uzyskania odpowiedzi są dogłębne wywiady przeprowadzone w 2016 roku z 27 wysokiej rangi generałami izraelskimi reprezentującymi Wywiad Wojskowy (Aman), Wywiad Cywilny (Mossad), Służby Bezpieczeństwa Ogólnego (Shabak), Rady Bezpieczeństwa Narodowego (Malal), Wydziału Planowania Sztabu Generalnego (Agat) oraz grupą doradców ds. bezpieczeństwa Premiera Izraela. W wywiadach zwrócono uwagę na trzy perspektywy spojrzenia na problem wpływu osiedli na bezpieczeństwo narodowe Izraela. Pierwsza wskazuje, że osiedla mają istotny wpływ na bezpieczeństwo Izraela, zaś druga perspektywa wskazuje, że są dla niego znaczącym obciążeniem. Trzecia wskazuje, iż problem osiedli nie jest istotny, gdyż można stwierdzić, iż skoro nikt nie pyta o znaczenie Tel Awiwu dla Izraela, więc konsekwentnie, dlaczego miałby pytać o wpływ osiedli. Używanie argumentów dotyczących bezpieczeństwa jest powszechne zarówno w Izraelu, jak i wielu innych państwach, dotyczy to zwłaszcza wyzwań bezpośrednio z nim związanych. Szczegółowy punkt widzenia reprezentowany przez Izraelskie Elity Bezpieczeństwa Narodowego (INSE) pozwala na wyodrębnienie fachowych i racjonalnych uzasadnień, spośród politycznego, zwodniczego jazgotu. Artykuł może wzbudzać zainteresowanie zarówno osób zajmujących się problematyką bezpieczeństwa ogólnie, jak i konfliktem Izraelsko-Palestyńskim w szczególności.
Wpływ osiedli na Zachodnim Brzegu na bezpieczeństwo narodowe Izraela
Keywords: Israeli Palestinian conflict; national security elite; settlements, peace; konflikt izraelsko-palestyński; bezpieczeństwo wewnętrzne; osadnictwo; pokój